The relationship between migraine and Hashimoto’s thyroiditis: a single center experience - Nowaczewska, Magdalena; Straburzyński, Marcin; Meder, Grzegorz; Waliszewska-Prosół, Marta (Frontiers in Neurology, 2024)
Introduction: Hashimoto's thyroiditis (HT) is nowadays the leading cause of hypothyroidism with high and still growing prevalence in general population, but there are lack of data regarding migraine and HT connection.Methods: The aim of this study was to analyze the prevalence of HT in migraine and to check if the presence of HT influence migraine severity. This retrospective observational cohort study involved consecutive migraine patients consulted at our Headache Centre with diagnosis of migraine. Electronic charts of patients were collected, including data on migraine type, presence of cranial autonomic symptoms (CAS), monthly migraine days (MMD), medication overuse headache (MOH), and the presence of comorbidities including HT.Results: We found 928 eligible migraine patients, 88.7% were women. The mean age was 36,09 years. 592 (63.8%) were diagnosed with episodic migraine (EM), the rest with chronic migraine (CM). MOH was additionally diagnosed in 258 (27,8%) patients. The duration of migraine was 15,99 years. 106 (11.4%) was diagnosed with HT, 148 (15.9%) with hypothyroidisms, while 84 (9,05%) had both diagnosis. Migraine patients with HT were significantly older (p<0.001), were more frequently women (p=0.0017), had longer duration of migraine (p<0.001), had CAS more frequently (<0.001), developed CM (p=0.0169) and depression more frequently (p=0.0047) and had more MMD (p=0.0195) as compared with individuals without HT. According to our multivariate logistic model, the presence CM was positively associated with HT (OR 1.76, p=0.045), MOH and duration of migraine, while negatively associated with aura.Conclusions: HT is very prevalent in migraine patients. This is the first study considering migraine and HT to be comorbid and suggesting that HT may influence the course of migraine causing its chronification.